Formulation and evaluation of hair dye shampoo using Genipa americana L. (Huito) fruit extract - Dany Gutierrez-Ninachoque, Jimmy Oscar Ortiz de Orue-Meza, Carla del Carpio-Jiménez (Journal of Applied Pharmaceutical Science, 2024)
Natural dyes are in demand due to their inherent goodness and minor side effects. However, color fastness and poor reproducibility after application in human hair still need to be improved for natural hair dyeing. This study investigates the efficacy of Genipa americana fruit coloring extracts for hair dyeing. The dye was extracted from green fruit using a hydroalcoholic solution of 70% ethanol and 30% water. The study analyzed the physicochemical properties of the shampoo dye and evaluated its microbiological quality. The study also assessed the ability of the coloring shampoo to dye bleached hair by measuring the total color difference using a tristimulus colorimeter. The shampoo was applied for one month, with different numbers of applications (30, 15, and 10) and concentrations of 7.5% and 10% of the extract. A tress of bleached hair was also used as a control, but it did not receive any treatment. The results showed that the physicochemical characteristics were within the parameters established for this type of formulation. Likewise, the microbiological quality was satisfactory. Regarding the coloring capacity, it was shown that the 10% formulation presented the most significant color difference concerning the hair of the bleached tresses after 30 applications of 45 minutes each compared to the control. It was also shown that the concentration of G. americana extract directly affected the coloring.
Keywords: Natural dye, hydroalcoholic extraction, tristimulus colorimeter, hair dye formulation, Genipa americana